High Temperature Corrosive Environment in a Sintering Plant for Pig Iron Production and Its Effect on Different Steel Grades. Issue 8 (20th February 2017) - Rojacz, Harald; Krabac, Lubomir; Varga, Markus; Adam, Karl; Fafilek, Günter
Abstract : The harsh environment in a sintering plant for pig iron production leads to high temperature corrosion of the sinter grates. In the present study, a detailed analysis of the corrosives in such applications is given to understand materials failure. Various steels are tested, revealing effects of various alloying concepts, the resulting phases and their corrosive behavior in this complex corrosive environment at ≈900 °C. In order to understand the underlying corrosion mechanisms, detailed analyses are performed. Results indicate mainly chlorine, sulfur, and oxidation based corrosive decay at elevated temperature and a high relevance of protecting alloying elements within the steels. Abstract : This study examines high temperature corrosion effects of sintering plants in the pig iron production. A thorough examination of corrosives is given. Materials exposed to such environment suffer from high temperature oxidation and molten salt corrosion at 900°C with chloride and sulphide species. A high relevance of corrosive behaviour to the alloying elements (Cr, Ni, Mn, Si, Ti) is found.